Integration of leadership styles and its impact on work motivation and managerial effectiveness in Islamic banking‎ - Bahari, Samsul; Al Zarliani, Wa Ode; Sumail, La Ode; Hapsari, Indri; Bugis, Hairudin; Hasddin, Hasddin (Universitas Islam Indonesia, 2025)
IntroductionIn today’s dynamic and competitive organizational landscape, leadership is a critical determinant of work behavior, motivation, and managerial effectiveness. In the Indonesian Islamic banking sector, leadership presents unique challenges due to the need to balance operational efficiency with Islamic ethical and spiritual values. Despite asset growth, reports from the Financial Services Authority (OJK) highlight stagnation in organizational effectiveness attributed to weak employee motivation and commitment. While Islamic leadership has shown potential to enhance work culture and motivation, its integration into management practices remains inconsistent.ObjectivesThis study aims to empirically examine the effects of transformational and transactional leadership styles on managerial effectiveness, mediated by Islamic leadership and work motivation, within the context of Indonesian Islamic banking. The study addresses gaps in the literature regarding the mediating role of Islamic values and work motivation and compares the effectiveness of two dominant leadership styles in a religious-based organizational setting. MethodUsing a quantitative explanatory research design, the study surveyed employees from three Islamic bank branches in Kendari, Southeast Sulawesi, Indonesia. The total sample consisted of 57 respondents selected through purposive total sampling. Data were collected via a structured questionnaire using validated Likert-scale instruments. Data analysis employed Structural Equation Modeling–Partial Least Squares (SEM–PLS) using SmartPLS to evaluate both measurement and structural models, ensuring robustness for small sample sizes and non-normal data distributions. ResultsThe analysis revealed that both transformational and transactional leadership significantly influenced managerial effectiveness, with Islamic leadership and work motivation acting as partial mediators. Transformational leadership demonstrated a stronger direct and indirect effect compared to transactional leadership. Islamic leadership emerged as a pivotal mediating variable that bridged modern leadership styles with religious organizational contexts, enhancing motivation and managerial outcomes. ImplicationsThe findings provide theoretical insight by introducing a new conceptual model positioning Islamic leadership as a core mediating construct in leadership dynamics. Practically, the study offers actionable strategies for Islamic bank leaders to align spiritual values with performance targets, informing policy development and training programs on Islamic leadership capacity building.Originality/Novelty Despite growing interest in leadership models in Islamic organizations, few studies have systematically examined the mediating roles of Islamic leadership and work motivation in linking transformational and transactional leadership styles to managerial effectiveness—particularly within the Indonesian Islamic banking sector. Moreover, comparative evaluations of these two leadership styles in religious-based institutions remain underexplored. Addressing this gap, the present study proposes an integrative model that reflects both the spiritual context of Islamic organizations and modern leadership theory.